1993
DOI: 10.1093/intimm/5.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Rapid acceleration of neutrophil apoptosis by tumor necrosis factor-α

Abstract: We demonstrate here that human necrosis factor-alpha, a potent neutrophil activator, induces rapid (within 3 h) apoptosis of these cells, i.e. neutrophils treated with this cytokine exhibit (i) light and electron microscopic changes characteristic to apoptotic cells, (ii) reduced propidium iodide binding to DNA, and (iii) the ladder form of DNA, as shown by agarose gel electrophoresis. These results suggest that apoptosis acceleration may be involved in processes by which neutrophils are prevented from damagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(72 citation statements)
references
References 0 publications
6
66
0
Order By: Relevance
“…The results of a study by Coxon et al [32] attribute a major role to CD11b/CD18, a ␤ 2 integrin, in triggering apoptosis in activated, as opposed to resting, neutrophils, thereby regulating the magnitude of neutrophil extravasation to the TG-inflamed peritoneum of mice. Neutrophils also are sensitive to apoptosis induced by TNF-␣ or IL-6 [28][29][30][31], two cytokines known to be involved in inflammatory responses [56]. Furthermore, Fas is but one member of a recently discovered family of so-called death factor receptors that also includes the TNF receptor I, DR3/WSL-1, and CAR1 [see ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a study by Coxon et al [32] attribute a major role to CD11b/CD18, a ␤ 2 integrin, in triggering apoptosis in activated, as opposed to resting, neutrophils, thereby regulating the magnitude of neutrophil extravasation to the TG-inflamed peritoneum of mice. Neutrophils also are sensitive to apoptosis induced by TNF-␣ or IL-6 [28][29][30][31], two cytokines known to be involved in inflammatory responses [56]. Furthermore, Fas is but one member of a recently discovered family of so-called death factor receptors that also includes the TNF receptor I, DR3/WSL-1, and CAR1 [see ref.…”
Section: Discussionmentioning
confidence: 99%
“…FasL/Fas interactions might be expected to play a role in triggering the apoptosis of neutrophils at an inflammatory site. Neutrophils also possess several receptors besides Fas that could trigger their apoptosis, including receptors for the inflammatory cytokines TNF-␣ and IL-6, and for the ␤ 2 integrin CD11b/CD18 [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-␣ has been variably reported either to induce, delay, or have no effect on neutrophil apoptosis (6,(23)(24)(25). These contrasting results could be explained, at least in part, by recent findings of Murray et al (26), who showed that although prolonged incubation (Ͼ18 h) of human neutrophils with TNF-␣ indeed causes a decrease in the extent of apoptosis, TNF-␣ can induce apoptosis in a proportion of cells at earlier times (Ͻ8 h).…”
Section: Promotion Of Neutrophil Apoptosis By Tnf-␣mentioning
confidence: 99%
“…The up-regulation of Fas on neutrophils from RSV þ NPA suggests that the accelerated neutrophil apoptosis may be mediated through a Fas pathway. TNF-a is one of the cytokines known to accelerate neutrophil apoptosis [25][26][27]. RSV-infected macrophages have been reported to produce TNF-a [28] and RSV infection of epithelial cells could release TNF receptor type I (TNF-RI) [29].…”
mentioning
confidence: 99%